Review of the Performance of In-situ Foamed Bitumen Stabilised Pavements in the City ofCanning - Leek, Colin (Australian Geomechanics Society, 2011)
This paper reviews the results of research undertaken into the stiffness and fatigue performance of in-situ foamed bitumen stabilised pavement materials at various sites in the Cities of Canning and Gosnells in Western Australia. The aim of the research was to determine if a design relationship could be developed to predict the fatigue life of in-situ foamed bitumen stabilised pavements, and if the visco elastic properties of the bitumen binder were reflected in the stiffness and fatigue performance. The report also documents the performance of some of the earlier pavements now 11 years old, and reports on the results of recent trials in Nicholson Road and Vahland Ave where trails with lime and cement active binders were undertaken to determine the early strength of the pavements.